How Borders Come to Matter? The "Physicality" of the Border in Gloria Anzaldúa’s "Borderlands/La Frontera" - Melina Pereira Savi (Anuário de Literatura, 2015)
In this piece I attempt to address the ways in which Gloria Anzaldúa, in Borderlands: La Frontera (2007), negotiates the idea of the border as having both discursive and material dimensions. In creating a new mestiza consciousness from the borderland, which is the space that is affected by the borderline, Anzaldúa develops concepts and ideas that can be linked to Donna Haraway’s articulation of the cyborg and to Karen Barad’s theory of an agential realist ontology in the sense that Anzaldúa engages creatively with contradicting parts of her identity in a cyborgian fashion, and sees the enactment of borders as both limiting and empowering, as having emotional and material effects. Anzaldúa then addresses these effects and demonstrates how she applies them in the fabrication of a new consciousness, the consciousness of the new mestiza. In this work, therefore, I explore how the border makes itself physically present in Anzaldúa’s Borderlands and how the discursive meets matter; and I do this by finding common threads and possible connections among the works of Anzaldúa, Haraway, and Barad.